Co-occurrences among interrogation tactics in actual criminal investigations - Kaplan, Jeffrey (Psychology, crime & law, 2022)
During police interrogations, trained investigators may use different tactics to elicit information from criminal suspects. Through this exploratory research, we investigated which tactics were used most frequently by investigators in actual police interrogations and how they used tactics in combination. We coded 50 videotaped interrogations recorded in North America for 25 unique tactics as they were used by investigators. We divided each interrogation into 3-minute time blocks, counted the tactics that were used within each time block, and conducted a principal component analysis on those frequencies. We expected our analyses to reveal patterns of tactic use but had no a priori hypotheses about how investigators would combine and sequence interrogation tactics. Presenting evidence was the most common tactic, and investigators used minimization more than maximization tactics. The tactics grouped into seven components, indicating that they had been used by investigators within the same time blocks. Post hoc examination of those components revealed that tactics used in temporal proximity shared logical connections and segued into one another to form multifaceted persuasive messages. For instance, making accusations and increasing suspects’ guilt were often employed before offering justifications. This research provides insight into how interrogation tactics relate to one another during police interrogations.